ENHANCING GENERATION Z’S ROLE AS DIGITAL NATIVES AND CREATIVE MINDS IN ENTREPRENEURSHIP THROUGH SELF-EFFICACY - Sari, Vinnetti Ratna; Soelaiman, Lydiawati (Graduate Program of Universitas Tarumanagara, 2025)
The low level of entrepreneurship in Indonesia needs special attention. Generation Z, which is known as digital natives and has a creative spirit, is expected to be able to generate innovative ideas and take advantage of digitalization to build entrepreneurship. This study aims to determine the effect of digital competence and creative personality on entrepreneurial interest mediated by self-efficacy. The method used in this research is descriptive quantitative. Sample collection uses a non-probability sampling method with a purposive sampling technique. A total of 262 samples, namely Generation Z represented by vocational high school students and university students in Jakarta, were used in this study. Data analysis was conducted using Partial Least Square-Structural Equation Modelling (PLS-SEM). Based on the results of outer loading testing, it is known that all indicator statements are valid and reliable. The results of hypothesis testing state that digital competence and creative personality have a significant effect on self-efficacy. In addition, digital competence and self-efficacy affect Generation Z’s entrepreneurial interest. However, this study did not find a significant correlation between creative personality and entrepreneurial interest. This study found that self-efficacy fully mediates between creative personality and Generation Z’s entrepreneurial intention.